The Effect of Cultivating Rhizopora mucronate sp with Domang Method on Mangrove Survival Rate in Klayas Village - Bambang Respati; Bambang Imawan; Agus Kurniawan; Pratama Bimo Purwanto (Prospect Publishing, 2023)
Mangroves are one of the coastal plants that have various benefits. One of the benefits of mangroves is preventing abrasion. However, in some cases the survival rate for the mangroves is low due to various influencing factors, one of which is water conditions. Therefore, intervention is needed to increase the survival rate of mangroves. One intervention that can be carried out is by implementing Domang (Donat Mangrove) planting method which aims to protect mangrove seedlings from extreme water conditions. This method was implemented in Klayas Village which is in the strait area. This research aims to determine the effectiveness of the implementation of Donat Mangrove in increasing the survival rate of mangroves in Klayas Village. So far, the survival rate for mangrove planting in Klayas Village is only around 12% due to the extreme water conditions. However, Donat Mangrove method effectively increases the survival rate of mangrove planting by up to 31%. This shows that the application of Donat Mangrove planting method is effective in increasing the survival rate of mangroves in Klayas Village.